Structure of research abilities of bachelors of physical education and sport. - Omelyanenko G.A (Kharkov National Pedagogical University, 2010)
Clarification of concept «research abilities», «research abilities», «research abilities of bachelors of physical education and sport», is resulted in the articles. The basic aspects of research activity are considered, modern classifications of research abilities and the structure of research abilities of bachelors is certain from physical education and sport. It is revealed seven groups in the structure of a system of scientific-research abilities of bachelors of physical education and sport. The characteristic of a system of scientific-research abilities of bachelors of physical education and sport was defined with the help of theory of graphs.